Peran EWOM dan Perceived Ease Of Use sebagai Variabel Independen dalam Meningkatkan Customer Loyalty Pada Shopee dengan Customer Satisfaction sebagai Variabel Intervening - Idyatul Fitriani; Ibnu Khajar (Lembaga Yasin AlSys, 2026)
The development of digital technology and the increasing use of marketplaces have intensified competition among e-commerce platforms, including Shopee, making customer loyalty a key factor for long-term business sustainability. Customer loyalty is determined not only by the functional aspects of an application, but also by the information received by consumers and their platform-use experience, positioning electronic word of mouth (eWOM) and perceived ease of use (PEOU) as important variables, with customer satisfaction serving as a mediating variable between these factors and customer loyalty. This study aimed to analyze the role of eWOM and PEOU in influencing customer loyalty among Shopee users, with customer satisfaction as an intervening variable. A quantitative survey approach was employed by administering questionnaires to 300 Shopee users in Semarang City, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that eWOM and PEOU had a positive and significant effect on customer satisfaction; eWOM also had a positive and significant direct effect on customer loyalty, whereas PEOU had a negative yet significant effect on customer loyalty. These findings indicate that ease of use alone is insufficient to build loyalty and may even lower switching costs, thereby making it easier for customers to move to other platforms. In addition, customer satisfaction had a significant effect on customer loyalty and functioned as an intervening variable in the relationship between eWOM and PEOU and customer loyalty. The implications of this study underscore the need for e-commerce managers to strengthen positive eWOM and strategically manage application features in order to create sustainable customer satisfaction and loyalty.